Determining the Effects of High Phytase Levels and Feeding Duration on Growth Performance and Carcass Characteristics of Growing-Finishing Pigs - C. M. Vier; S. S. Dritz; M. D. Tokach; J. R. Bergstrom; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 1,215 barrows and gilts (PIC; 359 × Camborough; initially 61.5 ± 1.02 lb) were used in a 126-d growth trial to determine the effects of high phytase levels and feeding duration on growth performance and carcass characteristics of growing- finishing pigs. Pens of pigs were randomly assigned to 1 of 3 dietary treatments with 15 pens per treatment and 27 pigs per pen. The experimental diets were fed in four phases and based on corn, distillers dried grains with solubles (DDGS), and soybean meal. The 3 dietary treatments consisted of: 1) Control (diets formulated with no added phytase); 2) Grower phytase (diets formulated with 1,500 phytase units (FYT)/kg added phytase fed from d 0 to 57, then no phytase from d 57 to market); and 3) Grow-finish phytase (diets formulated with 1,500 FYT/kg added phytase fed throughout the entire study). The phytase-containing diets had the addition of 1,500 FYT/kg of Ronozyme HiPhos 2500 (DSM Nutritional Products, Inc., Parsippany, NJ) with assumed release values of 0.146% standardized total tract digestible (STTD) P, 0.166% available P, 0.102% STTD calcium, 24 kcal/lb of metabolizable energy, 19 kcal/lb of net energy, and 0.0217, 0.0003, 0.00886, 0.0224, 0.0056, 0.0122, and 0.0163% digestible Lys, Met, Met + Cys, Thr, Trp, Ile, and Val, respectively. Beef tallow and feed grade amino acids were added to the diets without phytase to balance the net energy and standardized ileal digestible (SID) amino acid concentrations across treatments. During the grower period (d 0 to 57) pigs fed the control diets with no added phytase had increased average daily gain (ADG) compared to pigs fed phytase in the grower period, with pigs fed phytase in the grower and finishing stages intermediate. Pigs fed the phytase-containing diets had poorer feed efficiency (F/G) compared to pigs fed the control diets with no phytase. During the finisher period, ADG and F/G were similar between pigs fed the control and grower phytase treatments, and both were better (P<0.05) than for pigs fed the phytase in grower and finisher. Overall, pigs fed diets with no phytase and pigs that were only fed phytase in the grower period had improved (P<0.05) ADG and F/G than pigs fed the phytase-containing diets fed until market. There was a marginally significant (P<0.10) treatment effect on hot carcass weight (HCW), with pigs fed the control and grower phytase treatments having greater HCW than the pigs fed phytase throughout treatment. No evidence of differences (P>0.10) were observed for other carcass characteristics. In summary, adding 1,500 FYT/kg of phytase and using full matrix values for minerals, amino acids (AA), and energy had detrimental effects on ADG, F/G, and HCW in this study. We speculate that the negative effects on performance of pigs fed added phytase may be due to overestimating the matrix values for energy and AA and further research is warranted.
Keywords: growing-finishing pigs; phytase; super-dosing; withdrawal